Exploring Best Practices for Innovation Management in a Rapidly Changing Business Environment - Kim Thiên Di (Journal of Management and Administration Provision, 2022)
This thesis investigates successful strategies for managing invention in a dynamic business setting. This research uses a combination of qualitative interviews with business leaders and supervisors and a quantitative survey of company staff. The qualitative data identifies several best practices for innovation management, including continuous scanning of the external environment, cross-functional collaboration and teamwork, agility and flexibility, clear innovation strategy and vision, risk-taking and experimentation, resource allocation and management, leadership support and commitment, customer-focused innovation, and embracing digital transformation. The quantitative survey data reveals that while the majority of organizations have formal innovation strategies and cultures that encourage innovation, there is room for improvement in terms of having formal innovation processes, dedicated resources, formal metrics, and collaborations with external partners. Moreover, the results of the poll show a causal link between innovative management practices and particular leadership traits. Leaders who communicate a clear vision for innovation, encourage risk-taking and experimentation, allocate resources for innovation, provide support and guidance, and encourage cross-functional collaboration are more likely to drive successful innovation management practices within their organizations. Insights and suggestions for organizations to enhance their innovation management practices and maintain competitiveness in a dynamic business climate are provided by this study's results. Organizations can effectively navigate the innovation challenges and achieve sustainable growth and success if they adopt the identified best practices and exhibit the proper leadership behaviors.